Social network proximity predicts similar trajectories of psychological states: Evidence from multi-voxel spatiotemporal dynamics - Ryan Hyon; Adam M. Kleinbaum; Carolyn Parkinson (NeuroImage, 2020)
Homophily is a prevalent characteristic of human social networks: individuals tend to associate and bond with others who are similar to themselves with respect to physical traits and demographic attributes, such as age, gender, and ethnicity. Recent research using functional magnetic resonance imaging has demonstrated a positive relationship between individuals’ real-world social network proximity (i.e., whether they are friends, friends-of-friends, or farther removed in social ties) and inter-subject correlation (ISC) in their time series of neural responses when viewing audiovisual movies. However, conventional ISC methods only capture information about similarity in the temporal evolution of region-averaged neural responses, and ignore information carried in fine-grained, spatially distributed response topographies. Here, we demonstrate that temporal trajectories of multi-voxel response patterns to naturalistic stimuli are exceptionally similar among friends and predictive of social network proximity, over and above the effects of response magnitude fluctuations. Furthermore, inter-subject similarity in the temporal trajectory of multi-voxel response patterns across distant points in time was particularly positively associated with individuals’ proximity in their real-world social network. The fact that exceptional similarities among friends were most pronounced in long-range temporal fluctuations of response patterns located in multimodal cortical regions (e.g., regions of posterior parietal cortex) suggests that aspects of high-level processing during naturalistic stimulation may be particularly similar among friends. Given the localization of results, we speculate that socially close individuals may be particularly similar in endogenously driven shifts in how they distribute their attention (e.g., across the environment, within internal representations) over time. These results suggest that friends may experience exceptionally similar trajectories of psychological states when exposed to a common stimulus, and, more generally, that there are meaningful individual differences in the temporal evolution of multi-voxel response patterns during naturalistic stimulation.